Seasonal shift in soft bottom-dwelling community structure in coastal waters of the northern Bay of Bengal, Indian Ocean - Al Abdullah, Mamun; Alam, Md. Didarul; Akhtar, Aysha; Mustafa Kamal, Abu Hena; Islam, Md. Saiful; Alam, Md. Wahidul; Forruq, Rahman Muhammed; Uddin, M. Muslem; Xu, Heng Long (National Institute of Science Communication and Information Resources, 2018)
Benthic invertebrate communities play an important role in functioning of benthic food webs and commonly used as potential biomarkers in environmental monitoring programs. The seasonal variation in community structures of macro benthos was studied in northern Bay of Bengal, Bangladesh from summer 2015 to spring 2016. A total of 45 species belonging to 35 families, 25 orders and 5 classes were identified. Of these species, 14 were commonly distributed and 10 were highest contributors. The species number, total abundance and species richness peaked in summer and sharply dropped in winter whereas evenness and diversity were highest in spring and both were lowest in winter. Multivariate analysis (CAP and RELATE) revealed a clear significant seasonal shift in community patterns of the benthic communities with relation to environmental variables. Further, BIOENV signified that water temperature, salinity, dissolved oxygen and water nutrients were the main drivers to shape the community structure. These finding suggest that seasonal shift in benthic communities in response to environmental changes might be used as bio indicators for discriminating environmental quality status in coastal ecosystems.